The Massacre of Syrian Christians at Tur Abdin - Henno, Suleyman. (Piscataway, NJ)
iv, 181 sayfa
Keywords: “The present volume is a first hand account of the atrocities suffered by the Syrian Christians at Tur Abdin during the genocide of 1915 by Suleyman Henno“ -- Yayıncı.